Long Bean—an Asian Vegetable Emerging in Florida - Kshitij Khatri; Guodong Liu; Qingren Wang; Yuncong Li; David Dinkins; Bonnie Wells (EDIS)
Food diversity, nutritional food supply, and profitability are the priorities of agricultural and horticultural industries. To diversify vegetable products and increase the Florida vegetable industry's competitiveness, a number of new vegetable crops are rapidly emerging in the state. Due to Florida's favorable climate, these vegetable crops grow well and have high market potential. The objective of this 6-page fact sheet is to provide a general overview of long bean, one of the Asian vegetable crops grown in Florida. Written by Kshitij Khatri, Guodong Liu, Qingren Wang, Yuncong Li, David Dinkins, and Bonnie Wells, and published by the UF Department of Horticultural Sciences, October 2015.